2012
DOI: 10.1371/journal.pone.0052471
|View full text |Cite
|
Sign up to set email alerts
|

Normal Muscle Oxygen Consumption and Fatigability in Sickle Cell Patients Despite Reduced Microvascular Oxygenation and Hemorheological Abnormalities

Abstract: Background/AimAlthough it has been hypothesized that muscle metabolism and fatigability could be impaired in sickle cell patients, no study has addressed this issue.MethodsWe compared muscle metabolism and function (muscle microvascular oxygenation, microvascular blood flow, muscle oxygen consumption and muscle microvascular oxygenation variability, which reflects vasomotion activity, maximal muscle force and local muscle fatigability) and the hemorheological profile at rest between 16 healthy subjects (AA), 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 42 publications
8
31
0
Order By: Relevance
“…We recently reported that despite reduced hemoglobin concentration and hematocrit level in SCA patients, the local resting muscle oxygen consumption is comparable between SCA patients and healthy subjects because the local resting microvascular blood flow is increased in the former population [25]. Although the hemodynamic compensation for chronic anemia may be sufficient to normalize muscle oxygen consumption at rest, this is not the case during exercise where the needs for oxygen gradually increase with the intensity.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that despite reduced hemoglobin concentration and hematocrit level in SCA patients, the local resting muscle oxygen consumption is comparable between SCA patients and healthy subjects because the local resting microvascular blood flow is increased in the former population [25]. Although the hemodynamic compensation for chronic anemia may be sufficient to normalize muscle oxygen consumption at rest, this is not the case during exercise where the needs for oxygen gradually increase with the intensity.…”
Section: Discussionmentioning
confidence: 99%
“…20,22,23,39 Therefore, SC and SS children were analyzed separately. Part of the results described here were previously included in a report on the initial SAPOTILLE cohort.…”
Section: Comparisons Between Ss and Sc Childrenmentioning
confidence: 99%
“…Leg blood flow studies in young healthy men following acute lowering of haemoglobin concentration have demonstrated increased systemic and muscle blood flow (Koskolou et al, 1997;Gonzalez-Alonso et al, 2006)). Studies using strain gauge plethysmography (Eberhardt et al, 2003)and near infra-red spectroscopy (Waltz et al, 2012) have consistently shown increased resting overall forearm blood flow in SCD patients compared with controls. Animal studies of non-SCD anaemia show that resting skeletal muscle microvascular flow is significantly higher in the anaemic state compared with controls (Kubes et al, 1988).…”
Section: Discussionmentioning
confidence: 99%